Morbidity of pandemic H1N1 influenza in children with cancer. - Caselli, Désirée; Carraro, Francesca; Castagnola, Elio; Ziino, Ottavio; Frenos, Stefano; Milano, Giuseppe Maria; Livadiotti, Susanna; Cesaro, Simone; Marra, Nicoletta; Zanazzo, Giulio; Meazza, Cristina; Cellini, Monica; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: To define the mortality and the current impact of the H1N1 pandemic in pediatric hematology-oncology centers, we performed a specific survey. PROCEDURE: Pharyngeal swabs from patients with fevers of unknown origin, flu-like symptoms or bronchopneumonia were screened for H1N1 using PCR. RESULTS: Sixty-two patients with documented H1N1 infection were reported: 16 had recently stopped therapy, 2 were at the diagnosis stage, and 44 were receiving therapy. The clinical course was severe (requiring ICU admission) in only 1 patient, moderate (requiring hospital admission) in 38, and mild in the remaining 23 (37%), treated as outpatients. While none of the patients died of H1N1-related complications, two patients died of progressive cancer; in all of the remaining cases, symptoms resolved within 11 days. The clinical course was complicated by respiratory distress or bronchopneumonia in 10 cases. Oseltamivir was given to 82% of patients. Chemotherapy was temporarily withdrawn in 54% of cases for a median time of 21 days (range, 4-43 days). CONCLUSION: H1N1 infection in children with cancer was not reported as the cause of death in any case but resulted in reduced intensity of anti-cancer therapy.
Keywords: Adolescent; Antineoplastic Agents; Cause of Death; Child; Child, Preschool; Data Collection; Disease Outbreaks; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Leukemia; Lymphoma, Non-Hodgkin; Morbidity; Neoplasms; Treatment Outcome; Young Adult